EFEKTIVITAS PEMANFATAAN BAHAN AJAR PENDIDIKAN AGAMA ISLAM TERINTEGRASI SAINS UNTUK KELAS VIIA SMPN 38 SELUMA - Turiman Turiman (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2020)
This study aims to determine the Effectiveness of  Utilization of  Teaching Islamic education Integrated  Science Class VIIA SMPN 38 Seluma  Kecamatan Sukaraja Seluma  district academic year 2016 / 2017.  This type of research  is a developmen study  with the respondents of class VIIA students  SMPN 38 Seluma  And using data  collection  techniques through  question- naires  from teachers, peers  and  expert  tests after obtaining the data  determined the level of validity by using a checklist. The results of this study indicate  that the use of teaching  materials  of Integrated  Islamic Studies of Science  more  effectively used in the learning process  in comparison with previous  teaching  materials  with a comparison of 18 students  38.88% (only 7 people are categorized  pass) while 88.88% Material of Integrated  Islamic Religion Science  reaches  16 people  who are categorized  as graduated ).